2020
DOI: 10.5114/pg.2019.88622
|View full text |Cite
|
Sign up to set email alerts
|

The safety of upper gastrointestinal endoscopic biopsy in patients receiving antithrombic drugs. A single-centre prospective observational study

Abstract: Introduction: In July 2012, the Japan Gastroenterological Endoscopy Society updated their guidelines on gastroenterological endoscopy in patients undergoing antithrombotic therapy, although the safety of endoscopic procedures in patients receiving antithrombotic drugs has yet to be sufficiently studied. Aim: This study evaluates the safety of upper gastroenterological endoscopic biopsy in patients receiving antithrombotic drugs. We evaluated the prospective observational safety of endoscopic biopsy performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, patients with ANVUGIB requiring EG are often more complex, and the guidelines do not specify the circumstances under which biopsy of a suspected malignant lesion is performed, a situation in which the clinician mostly operates on the basis of their own clinical experience [3,12,16]. Clinicians often encounter the following difficulties in making decisions [17][18][19][20]: (1) Can biopsy be performed in patients with active bleeding under EG? (2) What are the levels of Forrest classification for active bleeding during EG that can be biopsied?…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with ANVUGIB requiring EG are often more complex, and the guidelines do not specify the circumstances under which biopsy of a suspected malignant lesion is performed, a situation in which the clinician mostly operates on the basis of their own clinical experience [3,12,16]. Clinicians often encounter the following difficulties in making decisions [17][18][19][20]: (1) Can biopsy be performed in patients with active bleeding under EG? (2) What are the levels of Forrest classification for active bleeding during EG that can be biopsied?…”
Section: Discussionmentioning
confidence: 99%
“…To update the evidence for the previous KSGE guidelines, we performed a literature search and identified eight retrospective and prospective cohort studies. 53,59,[73][74][75][76][77][78] Various low-risk endoscopic procedures, such as double-balloon enteroscopy, 73,78 diagnostic endoscopy, 53,75 endoscopic papillary large balloon dilatation, 76 or endoscopic biopsy, 59,77 were evaluated to determine whether warfarin could be continued or discontinued before the procedures. All included studies indicated that the overall rate of early or delayed hemorrhage did not differ between the warfarin interruption and non-interruption groups.…”
Section: Statementmentioning
confidence: 99%
“…11 Importantly, the available body of evidence suggests no significant differences in clinically relevant delayed bleeding between patients undergoing diagnostic EGD who do or do not take antithrombotic agents. [11][12][13][14][15] Also of note, in patients taking antithrombotic agents at baseline, available evidence suggests no differences in clinically significant bleeding outcomes when EGD (with or without biopsy sampling) is performed after appropriate periprocedural cessation of these agents 16 versus when they are continued leading up to and after the procedure. 11,17,18 Based on these and other data, the ASGE guideline on management of antithrombotic agents concludes that there is a low overall risk of bleeding during diagnostic EGD with or without biopsy sampling in patients on all antithrombotic medication.…”
Section: Bleedingmentioning
confidence: 99%